A practical approach to switch from a multiple pill therapeutic strategy to a polypill-based strategy for cardiovascular prevention in patients with hypertension. Issue 10 (October 2020) - Coca, Antonio; Kreutz, Reinhold; Manolis, Athanasios J.; Mancia, Giuseppe
Abstract : N/A: Pharmacological treatment recommended by guidelines for very high-risk patients with established cardiovascular disease (CVD) includes lipid-lowering drugs, antihypertensive agents and antiplatelet therapy. Depending on the associated comorbidities, this baseline regimen has to be complemented with other drugs. Therefore, the number of pills to be taken is usually high and adherence to these multiple pill therapeutic regimens and long-term persistence on treatment is low, being the main factor for insufficient control of cardiovascular risk factors. The CNIC (Centro Nacional de Investigaciones Cardiovasculares, Ministerio de Ciencia e Innovación, España) polypill is the only polypill containing low-dose aspirin approved by the EMA and marketed in Europe, and has demonstrated to improve adherence. For this reason, guidelines recommend its use for secondary prevention of CVD, and also for primary prevention of cardiovascular events in patients with multiple cardiovascular risk factors and advanced atherosclerotic process at high risk of thrombosis and low risk of bleeding. This article pretends to simplify the steps that clinicians may follow to switch from any baseline regimen to the polypill with the use of several algorithms and tables showing the equivalent effective daily doses of different angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers and statins to facilitate switching, as well as the steps to be followed depending of the initial levels of BP and LDL-cholesterol values to achieve BP and lipid control with the association to the polypill of other BP-lowering or lipid-lowering drugs whenever needed.